(untitled) - Watkins, Michael (Boston, Massachusetts, 2013)
In this updated and expanded version of the international bestseller The First 90 Days, Michael D. Watkins offers proven strategies for conquering the challenges of transitions—no matter where you are in your career. Watkins, a noted expert on leadership transitions and adviser to senior leaders in all types of organizations, also addresses today’s increasingly demanding professional landscape, where managers face not only more frequent transitions but also steeper expectations once they step into their new jobs.
Keywords: Organizational effectiveness,Hiệu quả tổ chức